Englishness and empire 1939-1965 - Webster, Wendy (Oxford University Press, 2007)
Did loss of imperial power and the end of empire have any significant impact on British culture and identity after 1945? This text analyses this question, as well as looking at aspects such as gender, race, empire, immigration and decolonization.